EFFECT OF HYPERTENSION AND SMOKING ON HEART RATE VARIABILITY IN PATIENTS WITH MYOCARDIAL INFARCTION - Saleem, Shemaila; Majeed, Syed Muhammad Imran; Moazzam, Sadia (Pakistan Journal of Physiology, 2018)
Dental College, Islamabad Background: Patients afflicted with myocardial infarction and hypertension are at increased risk of developing arrhythmias due to autonomic imbalance. Heart rate variability, a non invasive analytical measure, can be employed for evaluating the autonomic nervous system. Cigarette smoking increases the possibility of acute cardiac events associated with augmented sympathetic drive and endothelial dysfunction. Autonomic dysfunction is a known symptom of impaired cardiac activity and is robustly related with amplified overall mortality risk. This study aimed to identify heart rate variability (HRV) indices in hypertensive and non hypertensive individuals with acute myocardial infarction (AMI) and the effect of smoking on HRV of patients with AMI. Methods: Fifty patients with AMI underwent 24 hours holter monitoring. Time and frequency domain measures of HRV were analysed including SDNN, SDNNi, SDANN, rMSSD, pNN50, power, VLF, LF, and HF. Results: The time domain indices SDNN, SDANN, SDNNi, RMSSD and pNN50 were decreased in hypertensive patients when evaluated against non hypertensive patients with AMI. Frequency domain indices; The Total power, VLF, LF and HF amongst hypertensive and non hypertensive patients showed decreased HRV in hypertensive patients with AMI. SDNN, SDANN, SDNNi, total power, VLF and LF were decreased in smokers suffering AMI as compared to non smokers with acute myocardial infarction (p<0.05). Conclusions: Heart rate variability is diminished in hypertensive individuals after AMI. It reflects autonomic imbalance in individuals with co-existent hypertension and AMI. The study also suggested a noteworthy attenuation of time and frequency domain indices in the study population with smoking habits.